LOCUS DELICTIE TINDAK PIDANA HACKING DALAM PERSPEKTIF HUKUM POSITIF INDONESIA - Oos Ariyan; Moh. Zeinudin (PROSIDING, 2022)
Technology that is increasingly developing makes it easier for humans to do their jobs. However, with the development of technology, it has led to a growing crime known as cyber crime. Cyber crime can be in the form of hacking. In the existing legal regulations in Indonesia, to provide protection there is an electronic information and transaction law which is expected to provide legal protection and legal certainty. The regulation of locus delictie itself is contained in Article 84 of the Criminal Procedure Code which requires a clear determination of the locus delictie to determine the authority to try but in cyber crime cases it is not simple in traditional crimes. Hacking crimes sometimes have differences in the place where the incident occurred and the place of the perpetrator. The purpose of this study is to analyze and determine the determination of locus delictie in hacking crimes. By using normative legal research methods. The results of this study indicate that there are no rules governing the determination of locus delictie in cyber crimes. Thus, determining the locus delictie of hacking crimes can use the locus delictie theory, namely the theory of tools and the theory of consequences. Keywords: cyber crime, hacking, locus delict.